HUNIAN ADAPTIF SEBAGAI REVITALISASI PERMUKIMAN KUMUH KAMPUNG RAWA BENGEK - Natasha Jeanette Sapoetra (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2021)
Population growth and rapid urbanization have resulted in the growth of urban village clusters and have increased the urgency for habitable housing in slum settlements. So that a follow-up is needed to modify and restructure slum settlements in order to improve the quality of life of the community and improve the image of the urban village in the urban context. The concept of adaptive living for revitalization is one of the alternative solutions that can be applied by using an landscape urbanism approach to adjust conditions according to the city context and its surroundings as well as social, cultural and habitual adjustments of local residents. Social shelter is a residential concept that is applied in the design so that the intensity of the social activities of the population can be maintained. The application of a modular system in housing developments makes it easy to facilitate the construction process and is sustainable in its surroundings and is expected to spread and be applied to other slum settlements so that slum settlers can feel that they have a place to live according to the standard of habitability. Through the concept of adaptive housing towards future development it can be an alternative solution in dealing with slum settlements in the context of urban villages. Keywords: adaptive housing; revitalization; slum settlements; urban villages AbstrakPertumbuhan penduduk serta urbanisasi yang melesat cepat membuat tumbuhnya klaster-klaster kampung kota dan menyebabkan urgensi tempat tinggal yang layak huni pada permukiman kumuh semakin meningkat. Sehingga dibutuhkan tindak lanjut untuk memodifikasi serta penataan kembali terhadap permukiman kumuh agar dapat meningkatkan kualitas hidup masyarakat dan memperbaiki citra dari kampung kota dalam konteks urban. Konsep perencanaan hunian adaptif dalam revitalisasi menjadi salah satu alternatif solusi yang dapat diterapkan dengan menggunakan pendekatan lanskap urban untuk menyesuaikan kondisi sesuai dengan konteks kota dengan sekitarnya serta penyesuaian sosial, budaya dan kebiasaan penduduk setempat. Hunian sosial menjadi konsep berhuni yang diterapkan dalam perancangan sehingga intensitas kegiatan bersosial penduduk tetap dapat terjaga. Penerapan sistem modular pada hunian ditargetkan untuk memudahkan proses konstruksi dan untuk pengembangan berkelanjutan di sekitarnya serta diharapkan dapat menjalar dan diaplikasikan pada permukiman kumuh lainnya sehingga para pemukim kumuh dapat merasakan memiliki tempat tinggal sesuai standart kelayakan dalam berhuni. Melalui revitalisasi berbasis konsep hunian adaptif menuju pengembangan di masa depan dapat menjadi alternatif solusi dalam menghadapi permukiman kumuh dalam konteks kampung kota.